The adoption and scaling of stress-tolerant rice varieties: A sustainable climate adaptation strategy for smallholders - Nayak, Swati; Tyagi, Neeraj Kumar; Naveen, Jami; Khandai, Suryakanta; Hossain,S. K. Mosharaf; Srivastava, Ashish Kumar; Kumar, Virendar; Singh, Sudhanshu (MDPI Books, 2025)
Climate change hastens the degradation of ecosystems and has a detrimental influence on food production and the food chain. There is a decline in agricultural productivity owing to stress incidences, accentuated by the increasing variability in inter-annual and seasonal climatic patterns. This has made the smallholder paddy farmers of Assam extremely vulnerable. One of the prominent abiotic stresses in Assam is recurrent submergence, which poses a substantial challenge to rice cultivation in flood-prone regions during the Sali/wet season. Drought is also a significant abiotic stress for Assam, particularly for Sali rice, because of the increasing frequency and duration of dry spells. In addition to Sali rice, Boro/summer rice is also confronted with various other stresses. Boro rice is vulnerable to cold stress in the early stages and heat stress later, impacting productivity. Losing a crop season is detrimental to farmers’ livelihoods and the food system’s sustainability. Hence, it is critical to address low productivity in areas where extreme weather events are widespread and recurrent. The enhancement in abiotic stress tolerance in rice can potentially augment the production, productivity, and overall profitability of the food system. Therefore, it is crucial to adopt an appropriate adaptation strategy to overcome this threat. With seeds being a primary and essential input, the adoption of stress-tolerant rice varieties is a high-potential and highly affordable adaptation strategy to combat climate risks. The adoption and scaling of stress-tolerant rice varieties (STRVs) can be one of the most significant climatic risk adaptation approaches for the future.